CBIO-22. p53 GAIN-OF-FUNCTION MUTATIONS DRIVE SEX SPECIFIC EFFECTS ON GLIOMA TUMORIGENESIS. (9th November 2020) - Rockwell, Nathan; Warrington, Nicole; Rubin, Joshua
Abstract: Sex differences in malignant brain tumors are well-established: Males exhibit greater incidence and poorer survival. Understanding the biology behind these sex differences requires investigation of the pathways known to drive gliomagenesis. The transcription factor TP53 (p53) is one of the most commonly mutated genes in glioblastoma. Most p53 mutations are missense mutations in the DNA-binding domain that lead to the expression of a full length mutant p53 protein. These mutations can endow p53 with oncogenic gains-of-function through aberrant DNA binding and regulation of noncanonical cancer-promoting target genes. Previously, we analyzed patient mutation data and identified six p53 mutations with sex differences in prevalence. In this study, we developed an in vitro mutant p53 glioma model to investigate the sex specific effects of three p53 point mutations: R175H, Y205C, and Y220C (Mm R172H, Y202C, and Y217C respectively). Male and female astrocytes isolated from p53 flox/- mouse pups were transduced with a retrovirus expressing mutant p53, followed by a lentivirus expressing CRE recombinase to remove the endogenous WTp53. We then assessed cell proliferation, clonogenicity, and in vivo tumorigenesis in these cells. All three mutations assayed displayed sex differences in proliferation, with male cells overexpressing p53:Y202C and p53:Y217C growing faster than female cells, and female cells overexpressing p53:R172H growing faster than male cells. Male Y202C and Y217C expressing astrocytes also exhibited a trend toward greater clonogenicity compared to female astrocytes. This observation is supported by higher expression of the stem cell markers SOX2 and NESTIN in the male cells. We performed parallel flank injections of male and female astrocytes expressing each mutation or p53 KO. Only male astrocytes expressing p53:Y202C or p53:Y217C and female astrocytes expressing p53:R172H mutation were able to form tumors in vivo . Together, these data support a sex specific gain-of-function phenotype for three different p53 mutations observed in glioma.